2018
DOI: 10.1186/s12888-018-1915-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between dispositional empathy, psychological distress, and posttraumatic stress responses among Japanese uniformed disaster workers: a cross-sectional study

Abstract: BackgroundDisaster workers suffer from psychological distress not only through the direct experience of traumatic situations but also through the indirect process of aiding disaster victims. This distress, called secondary traumatic stress, is linked to dispositional empathy, which is the tendency for individuals to imagine and experience the feelings and experiences of others. However, the association between secondary traumatic stress and dispositional empathy remains understudied.MethodsTo examine the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…These individuals are likely imagining the experiences and feelings of others, especially those who have experienced a hardship related to the pandemic via secondary or tertiary anecdotal accounts, or featured social media stories. While beyond the scope of this study, there is an established line of research demonstrating associations between psychological distress, empathy, and traumatic responses (Bride, 2004;Nagamine et al, 2018). The suggested clinical recommendation for these findings is to continue to limit news exposure and internet usage related to the pandemic, for those with a psychological vulnerability to stress and anxiety, and especially for those who consider themselves empathic.…”
Section: Discussionmentioning
confidence: 92%
“…These individuals are likely imagining the experiences and feelings of others, especially those who have experienced a hardship related to the pandemic via secondary or tertiary anecdotal accounts, or featured social media stories. While beyond the scope of this study, there is an established line of research demonstrating associations between psychological distress, empathy, and traumatic responses (Bride, 2004;Nagamine et al, 2018). The suggested clinical recommendation for these findings is to continue to limit news exposure and internet usage related to the pandemic, for those with a psychological vulnerability to stress and anxiety, and especially for those who consider themselves empathic.…”
Section: Discussionmentioning
confidence: 92%
“…These outcomes are in accordance with our hypothesis 1. The balance of EC seems to be important for stressful situations, as distress and well-being are related to empathy [33], although other-oriented empathy could enhance secondary PTG [51]. Twenty subjects in this study showed chronic fatigue based on the CIS-J total scores (chronic fatigue; more than 76) [52].…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have shown the same relationship between individual characteristics and industry work. For example, disaster workers scoring high on measures of empathy scales were at risk for compassion fatigue (Nagamine et al, 2018), trauma treatment specialists with more lengthy experience in the field were less likely to report symptoms of compassion fatigue and burnout (Craig & Sprang, 2010), and therapists who feared working through trauma experience of torture survivors and had high advocacy for their patients presented higher risk for compassion fatigue (Deighton, Gurris, & Traue, 2007). Research examining compassion fatigue experiences of law enforcement professionals also showed a heightened prevalence of compassion fatigue symptoms in comparison to other mental health measures (Dabdoub, Baker, Craw, & Kernes, 2018).…”
Section: Compassion Fatigue In the Caring Professionsmentioning
confidence: 99%